Multimedia-Supported Genre-Based Instruction in EFL Reading: A Systematic Review - Nina Puspitaloka; Ermanto; Yetti Zainil (VELES Voices of English Language Education Society, 2025)
The increasing prominence of multimodal texts in digital learning environments has intensified the need for EFL reading instruction that integrates linguistic, visual, and interactive meaning-making. While the Genre-Based Approach (GBA) is well established for scaffolding genre awareness and literacy development, and multimedia is widely recognized for enhancing engagement and comprehension, research examining their integration remains fragmented. Addressing this gap, this study reports a Systematic Literature Review (SLR) of 35 empirical studies published between 2018 and 2025, conducted in accordance with the PRISMA 2020 guidelines. The review investigates (1) the pedagogical affordances and limitations of integrating interactive multimedia within GBA for EFL reading instruction and (2) the global implications of these insights for EFL pedagogy in digitally mediated contexts. The synthesis reveals that multimedia-supported GBA affords enhanced learner engagement and motivation, strengthened genre awareness through scaffolded instructional stages, improved reading comprehension via multimodal reinforcement, increased cultural relevance through localized materials, and support for higher-order cognitive processing. However, recurring limitations were also identified, including insufficient teacher preparedness, unequal access to digital resources, superficial use of multimedia as supplementary add-ons rather than pedagogically embedded scaffolds, and a lack of longitudinal evidence on sustained literacy development. Synthesizing evidence across diverse educational contexts, this review highlights the global relevance of multimedia-supported GBA while emphasizing the conditions necessary for its practical and equitable implementation.